Bile acid secretion in cystic fibrosis: evidence for a defect unrelated to fat malabsorption. Issue 9 (September 1986) - Weizman, Z; Durie, P R; Kopelman, H R; Vesely, S M; Forstner, G G
Abstract : In order to define basic biliary defects not related to steatorrhoea in cystic fibrosis, we studied 12 control and 18 cystic fibrosis subjects, with a wide range of pancreatic function. Duodenal aspirates were collected over three consecutive 20 minute periods, during continuous intravenous infusion of cholecystokinin and secretin using a marker perfusion technique, and analysed for pancreatic enzyme output (colipase, lipase, trypsin), bile acid output and concentration, and biliary lipids. Cystic fibrosis patients, at all levels of pancreatic function, had significantly reduced total bile acid output (mumol/kg/h) with delayed appearance of the bile acid peak, compared with control subjects. Actual duodenal bile acid concentrations were significantly higher in cystic fibrosis subjects than in controls, however, probably because of the markedly reduced water output shown in these patients. The lithogenic index was not raised in cystic fibrosis patients at any level of pancreatic function. The reduced bile acid output and the delayed peak appearance probably reflect a defect in gall bladder responsiveness which is independent of pancreatic function and steatorrhoea. Whether this defect is related to gall bladder filling or a defective peptide hormone response awaits further study.